1991
DOI: 10.1007/bf00403288
|View full text |Cite
|
Sign up to set email alerts
|

Production of islet cell antibodies from Epstein-Barr virus-transformed peripheral blood lymphocytes in Type 1 (insulin-dependent) diabetic patients

Abstract: Islet cell antibodies are usually detected in the sera of almost all Type 1 (insulin-dependent) diabetic patients within several months after onset of the disease. The antibodies then disappeared quite early during the course of the disease. The present study was undertaken to detect islet cell antibody-producing clones in peripheral blood lymphocytes of Type 1 diabetic patients whose islet cell antibodies could not be detected in sera. Epstein-Barr virus-transformed lymphocytes were employed to enhance the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We reported previously that ICA could be detected in 65% of ICA~ IDDM patients using the Epstein-Barr virus transformation and hybridoma technology (54). This evidence demonstrates that autoreactive memory B-cells for ICA are present in peripheral blood of IDDM and that ICA were produced through nonspecific stimulation of these memory B-cells.…”
Section: Discussionmentioning
confidence: 67%
“…We reported previously that ICA could be detected in 65% of ICA~ IDDM patients using the Epstein-Barr virus transformation and hybridoma technology (54). This evidence demonstrates that autoreactive memory B-cells for ICA are present in peripheral blood of IDDM and that ICA were produced through nonspecific stimulation of these memory B-cells.…”
Section: Discussionmentioning
confidence: 67%
“…It should be noted therefore, that the C-peptide levels in almost all patients with persisting positive ICA or 64K antibodies were undetectable despite increased titres of such antibodies. In addition, we have previously reported that ICA could be detected in 65 % of ICA-negative Type i diabetic patients by using the Epstein-Barr virus transformation and hybridoma technology [14]. This evidence demonstrates that ICA were produced through non-specific stimulation of the B lymphocytes in the peripheral blood of ICA-negative Type i diabetic patients.…”
Section: Discussionmentioning
confidence: 64%
“…ICA were detected by an immunoenzymatic method using fresh frozen sections of human pancreatic tissues and peroxidase-labelled protein A on serial dilutions of serum samples as previously described [6,13,14]. Using this method, our laboratory participated in the ICA Proficiency Test under the auspices of the Immunology and Diabetes Workshop and the evaluation of our results in the fourth ICA Proficiency Test were as follows: lab validity, consistency, sensitivity and specificity were 97 %, 95 %, 94 % and 100 %, respectively.…”
Section: Assay Of Lcamentioning
confidence: 99%